The Romance of Business: Ayn Rand Romanticism - A. V. Grigorovskaya (Научный диалог)
The origins of a romantic worldview in the work of Russian-born American writer and philosopher Ayn Rand (Alisa Zinovievna Rosenbaum, 1905-1982) is studied in the article. The analysis is based on the Russian and American versions of the romantic trend in literature, which differ in the interpretation of the romantic hero. Ayn Rand formulates his own understanding of romanticism, in which the determining factor for a romantic hero is the presence of will in relation to his own character and being. Comparing the texts of Rand and the representatives of business romance S. Mervin and G.K. Webster, Calumet K (1901), it can be noted that their characters are outwardly similar (they are responsible, principled, they can inspire others), but they differ on a deeper level. It is shown that the fate of humanity lies at the center of the story of Rand’s novels, and not just the comprehension of ways to solve another production problem. It is noted that her characters overcome contradictions, try to understand themselves. It is stated that Ayn Rand makes the task of his work precisely the overcoming of dualism, following the traditions of Russian literature on American ground: taking the efficacious man as a basis, she embodies in her heroes what the Russian romantics aspired to: create the ideal of a whole person who changes himself and the world around him.